ACTIVE CALCIUM REABSORPTION FOLLOWING KIDNEY TRANSPLANTATION - I. P. Yermakova; I. E. Borodulin; I. A. Pronchenko; N. P. Shmerko (Вестник трансплантологии и искусственных органов)
Active calcium and sodium reabsorption (ACR, SR) examination was performed in 125 renal recipients (RR) [78 with good renal function (GRF), 26 with chronic rejection(CR), 21 with cyclosporine nephrotoxity(CN)], 18 with bronchial asthma (36 estimation) receiving for a long time glucocorticoid therapy (EG) and 16 – with chronic renal disease in the initial stage of renal insufficiency (CRD). It was revealed elevated level of ACR in all patients being maximal in triple immunosupression therapy (cyclosporine, prednisolone, azathioprine) and minimal in double (prednisolone, azathioprine) therapy both in GRF and CR. There was reliable linear inversely proportional dependence between ACR and SR in all recipients receiving triple immunosupression and EG patients with analogous regression coefficient and free article. The latter was lower in group of health voluntaries. ACR value did not depend on parathyroid hormone level in all groups of patients. In summary elevated ACR in RR is the result of low SR and high glucocorticoid level in blood and did not depend on PTH.